Cultural adaptation to Brazilian Portuguese of the Face, Legs, Activity, Cry, Consolability revised (FLACCr) scale of pain assessment - Edna Aparecida Bussotti; Ruth Guinsburg; Mavilde da Luz Gonçalves Pedreira (Universidade de São Paulo, 2015)
AbstractObjective: to perform the translation into Brazilian Portuguese and cultural adaptation of the Face, Legs, Activity, Cry, Consolability revised (FLACCr) scale, with children under 18 years old, affected by cerebral palsy, presenting or not cognitive impairment and unable to report their pain.Method: methodological development study of translation into Portuguese and cultural adaptation of the FLACCr. After approval by the ethics committee, the process aimed at translation and back-translation, evaluation of translation and back-translation using the Delphi technique and assessment of cultural equivalence. The process included the five categories of the scale and the four application instructions, considering levels of agreement equal to or greater than 80%.Results: it was necessary three rounds of the Delphi technique to achieve consensus among experts. The agreement achieved for the five categories was: Face 95.5%, Legs 90%, Activity 94.4%, Cry 94.4% and Consolability 99.4%. The four instructions achieved the following consensus levels: 1st 99.1%, 2nd 99.2%, 3rd 99.1% and 4th 98.3%.Conclusion: the method enabled the translation and cultural adaptation of the FLACCr. This is a study able to expand the knowledge of Brazilian professionals on pain assessment in children with CP